Prevalence and awareness of anaemia among medical students - Anjum, Shabina; Dabi, Maydaa M.; Aldahlawi, Nouf A.; Dabi, Manar M. (International Journal Of Community Medicine And Public Health, 2024)
The prevalence of anemia, which is the most common cause for anemia, is 52% in women aged 15 to 49 years, as per WHO statistics. Health consequences of anemia include reduced immunity, increased morbidity, and impaired cognitive performance. The main objective of this article is to give insight on the significant impact of anemia on the individual's health and the whole country and the importance of raising awareness about anemia. A number of studies were viewed during this semester, which were about anemia which is a medical problem in which the number of RBCs or HB concentrations is below the normal value, some of studies were about the prevalence and risk factor of anemia, the other dealt with its complications and what is the treatment for it, and some talked about the classification of anemia and how to diagnose it. Anemia is a worldwide medical condition that affects individuals and even countries. Medical students are of increased risk of mild anemia, but anemia is slightly higher in females. Despite anemia in medical students is mild, it is still worrying because it may be due to bad habits in eating or resources of food present at hostels. As a result, efforts should be made to prevent anemia, especially in medical students.